Рeculiarities of radiation oxidation of aluminum surface in contact with water - Gadzhieva, N.N. (Вопросы атомной науки и техники, 2018)
The peculiarities of the oxidation process and the dynamics of the formation of oxide nanostructures on the
surface of aluminum and water at room temperature and under the influence of radiation were studied by IR
reflection-absorption spectroscopy, radiothermoluminescence and atomic-force microscopy. The role of
intermediate surface-active particles in the dynamics of changes in the process of aluminum oxidation in the
absorbed dose range of 0.5…120 kGy is considered. It is established that the formation of nanostructured films is
dominated by molecular oxygen and other oxygen-containingion radicals generated by gamma-irradiation. It is
shown that the radiation modification of the surface leads to a change in the morphology and topography of the
surface state and is accompanied by the formation of oxide nanostructures whose defectiveness is determined by the
irradiation time. A possible mechanism for the radiation oxidation of aluminum in the Al/ads. H₂O system is
discussed. Методами ІЧ відбивно-абсорбційної спектроскопії, радіотермолюмінесценції і атомно-силової
мікроскопії вивчені особливості процесу окислення і динаміка формування оксидних наноструктур на
поверхні алюмінію з водою при кімнатній температурі і при радіаційній дії. Розглянута роль проміжних
поверхнево-активних часток у динаміці змін процесу окислення алюмінію у області поглиненої дози
0,5…120 кГр. Встановлено, що при формуванні наноструктурних плівок основну роль відіграють
молекулярний кисень та інші кисневоскладові іон-радикальні групи, генеровані гамма-опроміненням.
Показано, що радіаційна модифікація поверхні призводить до зміни морфології і рельєфу поверхневого
стану і супроводжується формуванням оксидних наноструктур, дефектність яких визначається часом
опромінення. Обговорено можливий механізм радіаційного окислення алюмінію в системі Al/адс. H₂O. Методами ИК отражательно-абсорбционной спектроскопии, радиотермолюминесценции и атомносиловой микроскопии изучены особенности процесса окисления и динамика формирования оксидных
наноструктур на поверхности алюминия с водой при комнатной температуре и при радиационном
воздействии. Рассмотрена роль промежуточных поверхностно-активных частиц в динамике изменений
процесса окисления алюминия в области поглощенной дозы 0,5…120 кГр. Установлено, что при
формировании наноструктурных пленок основную роль играют молекулярный кислород и другие
кислородосодержащие ион-радикальные группы, генерированные гамма-облучением. Показано, что радиационная модификация поверхности приводит к изменению морфологии и рельефа поверхностного
состоянии и сопровождается формированием оксидных наноструктур, дефектность которых определяется
временем облучения. Обсужден возможный механизм радиационного окисления алюминия в системе
Al/адс. H₂O.